Understanding Task-Based Language Teaching - Muhammadiyevna, Davlatova Shaxnoza; o’g’li, Tog’ayev Azizbek Abduraxmon (Journal of Innovation in Education and Social Research, 2024)
The article is explored that the principles and practices of TBLT for developing language skills across listening, speaking, reading, and writing domains. By examining the theoretical foundations, key components, implementation strategies, and potential benefits of TBLT, we can gain insights into its effectiveness as an approach to language instruction.